A Context-Based Design Process for Future Use Cases of Autonomous Driving: Prototyping AutoGym - Walz, Steffen; Krome, S; Goddard, W; Greuter, S; Gerlicher, A (2015)
Autonomous cars are on the horizon, meaning passengers will no longer have to focus on driving leaving them with extra time for other activities, or engagements. However, research has focused primarily on safety related aspects of autonomous driving, overlooking the need to design for this new free time. This raises the question, how do we design new interactive experiences for the future of autonomous cars? In this paper, we present a design process derived from our research-through-design approach to explore possible everyday use cases of autonomous driving from an experience-focused perspective. We report details of the four methods that constituted, and influenced our design process and led to the creation of AutoGym, an exertion interface with context-based interactions suitable for future car-based commuting. The contribution is twofold: Foremost, our design process suggests guidelines on how to design and simulate future use cases of what we assume will constitute the autonomous driving experience. Secondly, we aim to inspire automotive user experience designers to pursue a context-based design approach by leveraging situational features which support experiences that are tailored and unique to autonomous driving.